TENSION HEADACHES AND PSYCHOVEGETATIVE DISORDERS - Akhmedova Dilafruz Bahodirovna (Web of Journals Publishing, 2023)
This paper presents an advanced approach to the problem of tension-type headache. The pathogenesis of tension-type headache includes different factors: information stress (and other types), lack of sleep and physical activity, postural disorders with the formation of myogenic trigger zones. The authors describe the formation of disadaptation syndrome as a type of reaction to chronic stress exposure, view diagnostic criteria, basic mechanisms of development and chronicity of tension-type headache. Several modern methods of medicamental and non-medicamental therapy are discussed.
Keywords: headache, tension-typeheadache, children, stress, aminophenylbutyric acid.